The role of shared study space in shaping graduate students' social networks. Issue 1 (8th December 2020) - Zhou, Yaoyi; Hua, Ying
Abstract : Purpose: The purpose of this paper is to study whether the use of a shared study space played a role in shaping graduate students' social networks by exploring how the copresence in space was related to the structure of friendship and advice networks. The authors first proposed two concepts of spatial copresence: measured spatial-temporal copresence and perceived copresence. The authors then examined the role of copresence through a case study of a shared study space occupied by 27 graduate students in the same department. Design/methodology/approach: Copresence relations were first constructed through a six-month room access history data set and self-reported data to examine whether measured spatial-temporal copresence was consistent with perceived copresence. Friendship and advice network relations were then analyzed with copresence, social media connections, class project collaboration relations and social homophily (nationality, gender, cohort) through quadratic assignment procedure (QAP) and MQAP analysis. Findings: The authors found that students who used the shared study space more often reported more friendship and advice ties. The perceived copresence and the measured spatial-temporal copresence were highly correlated. Copresence relations, as measured by survey and room access history, were both significantly correlated with advice relation, which was associated with perceived social support. Originality/value: This study contributes to the debate about whether "space" continues to play significant roles in graduate students' social networks in the context of flexible learning environments. The results also reveal new directions for research methods in studying spatial proximity in flexible settings.